2011
DOI: 10.1021/ja2032772
|View full text |Cite
|
Sign up to set email alerts
|

Pb2+ as Modulator of Protein–Membrane Interactions

Abstract: Lead is a potent environmental toxin that mimics the effects of divalent metal ions, such as zinc and calcium, in the context of specific molecular targets and signaling processes. The molecular mechanism of lead toxicity remains poorly understood. The objective of this work was to characterize the effect of Pb2+ on the structure and membrane-binding properties of C2α. C2α is a peripheral membrane-binding domain of Protein Kinase Cα (PKCα), which is a well-documented molecular target of lead. Using NMR and iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
97
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(109 citation statements)
references
References 60 publications
(159 reference statements)
11
97
1
Order By: Relevance
“…Recently, the C2 domain of PKCα was shown to bind Pb 2+ with high affinity, which can compete with Ca 2+ for an interaction with the C2 domain (Morales et al 2011). Further structural studies using NMR revealed that Pb 2+ and PI(4,5)P 2 synergistically enhanced each others affinity for the C2 domain (Morales et al 2012).…”
Section: Phosphoinositide Binding Modulesmentioning
confidence: 99%
“…Recently, the C2 domain of PKCα was shown to bind Pb 2+ with high affinity, which can compete with Ca 2+ for an interaction with the C2 domain (Morales et al 2011). Further structural studies using NMR revealed that Pb 2+ and PI(4,5)P 2 synergistically enhanced each others affinity for the C2 domain (Morales et al 2012).…”
Section: Phosphoinositide Binding Modulesmentioning
confidence: 99%
“…The CSP pattern in the low-concentration Cd 2+ regime is very similar to that observed previously for the binding of two Ca 2+ ions to C2α. 16 This suggests that no less than two Cd 2+ ions with similar affinities bind to the loop region. We used the fluorescence emission spectra of native tryptophan residues in C2α to estimate the affinity of Cd 2+ to the high-affinity CMBL site.…”
mentioning
confidence: 99%
“…This is in sharp contrast with Pb 2+ ions, whose coordination geometry in protein-bound state is different from that of Ca 2+ , yet their ability to drive the C2α-membrane association is comparable. 16 …”
mentioning
confidence: 99%
“…Several reports in literature detail ITC-based quantitative measurements of interactions between biological macromolecules, such as proteins [30][31][32][33][34][35] or DNA [36][37][38][39] and metal ions. In this work, ITC was utilized to characterize the thermodynamics of boric acid binding to ct-DNA.…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%